RANTAI NILAI (VALUE CHAIN) AGRIBISNIS KOPI ROBUSTA RAKYAT: STUDI KASUS DI KABUPATEN EMPAT LAWANG PROVINSI SUMATERA SELATAN - Putri Suci Asriani; Armeitha Suryani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
The absence of routine counseling and cooperatives that can work together also makes farmers still have to independently decide the direction of their business. In addition, the coffee processing industry is still very minimal. The majority of existing coffee products are sold in the form of dried coffee bean directly to collector traders. This study aims to analyze the value chain of coffee produced by value chain actors, and the potential for agribusiness development of robusta coffee in Karang Caya Village, Pendopo Barat District, Empat Lawang Regency. In this study, primary and secondary data were used which were analyzed using value chain analysis (VCA) and discussed in descriptive analysis. Research respondents involved were smallholder coffee farmers, agro-industry players, traders, and local government officials who understand the prospects for developing coffee farming in the research location. Based on the results of the study, it is known that there are 3 marketing channels for coffee, namely: farmers à subdistrict collectors à wholesalers à end consumers; farmers à end consumers; and farmers à coffee processors à end consumers. The dominance of farmers as the main actors in the activities of supply to marketing of coffee is very visible, the role of groups and other institutions is very minimal. Uneven distribution of values results in inefficient channels. This condition results in the price setting being carried out by the buyer (price setter) while the seller acts as the price taker.Key words: Robusta coffee, smallholder farmer, value chain